The role of Achillea millefolium in traditional medicine: A review of its use in different cultures - Maryam Jangjoo; Amirhosein Joshaghani; Fatemehzahra Tahernejadgatabi (Shahrekord University of Medical Sciences, 2023)
Background and aims: The Achillea genus, part of the Asteraceae family, is native to the Northern Hemisphere, from Europe to Asia. These plants thrive in temperate climates and are often found in dry or semi-dry conditions. This research aimed to examine the therapeutic uses of Achillea plants, drawing from traditional medicine texts and laboratory and clinical studies. Methods: This narrative review involved a comprehensive search of major scientific databases to gather information on Achillea and its extracts from native or endemic species within the Achillea genus. The review spanned several decades and utilized sources such as Google Scholar, Scopus, PubMed, Institute for Scientific Information Web of Science, and botanical and local books (1990 - present). Results: Achillea is a medicinal plant used for the treatment of gynecological problems, diabetes control, gastrointestinal disorders, side effects of cancer such as mucositis caused by chemotherapy and radiotherapy, skin reactions caused by radiotherapy, treatment of prostate cancer, breast cancer, cervical cancer, and human gastric cancer. Conclusion: Considering the role of medicinal herbs in improving the side effects of cancer, treating certain types of cancer, controlling diabetes, and treating gastrointestinal problems, it is recommended to use this plant as a complementary medicine alongside routine treatments.